Formation and objectification in Hegel. Bildung in Prologues and Introductions Abstract - Lizárraga Gómez, Adolfo (Anales del Seminario de Historia de la Filosofía, 2023)
This article deals with the concept of Bildung in Hegel translated as “formation”, seeking to show the fundamental character it has for him in his work, since the prologues and introductions of his main books: Phenomenology of Spirit, Science of Logic and Philosophy of Right. It is highlighted “formation” as continuous movement of objectification. On this basis, it is related to other concepts with which Bildung has been identified in languages such as Spanish, English and Portuguese: “education” and “culture”. It is exposed the dialectic identity between them and the place “formation” takes as point of origin or general. Finally, it is concluded on the fundamental relation of Bildung with “action” as substance to the universal existence.